2014
DOI: 10.1126/science.1252510
|View full text |Cite
|
Sign up to set email alerts
|

The cellular and molecular origin of tumor-associated macrophages

Abstract: Long recognized as an evolutionarily ancient cell type involved in tissue homeostasis and immune defense against pathogens, macrophages are being rediscovered as regulators of several diseases including cancer. Here we show that in mice, mammary tumor growth induces the accumulation of tumor-associated macrophages (TAMs) that are phenotypically and functionally distinct from mammary tissue macrophages (MTMs). TAMs express the adhesion molecule Vcam1 and proliferate upon their differentiation from inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
1,166
4
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,165 publications
(1,217 citation statements)
references
References 35 publications
42
1,166
4
5
Order By: Relevance
“…Tumor associated macrophages (TAMs) have been widely observed in different types of cancers and often constitute the dominant myeloid cell population in tumors [94]. During tumor initiation and malignant progression, macrophages build up bidirectional interacting networks with tumor cells and other cells of the tumor microenvironment.…”
Section: Pkb Regulated Macrophage Functionmentioning
confidence: 99%
“…Tumor associated macrophages (TAMs) have been widely observed in different types of cancers and often constitute the dominant myeloid cell population in tumors [94]. During tumor initiation and malignant progression, macrophages build up bidirectional interacting networks with tumor cells and other cells of the tumor microenvironment.…”
Section: Pkb Regulated Macrophage Functionmentioning
confidence: 99%
“…enzymes, proinflammatory cytokines, regulatory factors, interleukin-12 (IL-12), and are also involved in termination of tumor cells by secreting tumor necrosis factor-α (TNF-α), reactive oxygen species (ROS), and nitrogen species (RNOS). On the contrary, type II macrophages (M2) moderate the inflammatory response, eliminate cell wastes, promote angiogenesis and tissue remodeling, and release cytokines, including anti-inflammatory interleukin-10 (IL-10) (Mariani and Edwards, 2008;Gordon, 2003;Franklin et al, 2014).…”
Section: Obesity-driven Inflammation and Crcmentioning
confidence: 99%
“…4 Furthermore, while TAMs have been termed M2 or alternatively activated macrophages (AAMs), IL-4 ¡/¡ PyMT mice had normal proportions of TAMs (characterized as CD11b lo MHCII hi VCAM C cells that highly expressed itgax, the gene that encodes CD11c) and TAM differentiation was intact in the absence of lymphocytes, suggesting TAMs are not the same as classical AAMs. 9 Thus, it has been suggested that macrophage heterogeneity should not be simplified on a linear scale between M1 and M2, but should be described in terms of the diversity of points on a color wheel. 4 Future Therapy With CSF-1…”
Section: M1 and M2 Characterization Should Be Avoidedmentioning
confidence: 99%